2019
DOI: 10.24263/2304-974x-2019-8-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure and soy protein isolate combinations on the water holding capacity and texture of pork meat batters

Abstract: Introduction. The used of high pressure and soy protein isolate combinations to emulsion meat products could improve the quality, water holding capacity, texture and increase product yield. Materials and methods. Raw pork batters were prepared as follows: 400g pork meat, 80g pork back-fat, 70g ice water,10g NaCl; sample C2 had 10g soy protein isolate (2%); sample C3-20g soy protein isolate (4%). The vacuum packed batters were put into a high pressure vessel and were done with 200 MPa for 10 min at 10±2° C. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The G ′ values at 80°C of C1, C2, and C3 were 33.31, 48.43, and 44.08 kPa, respectively. The result was agreement with the result of hardness in our previous study (Sukmanov et al, ), C2 had the highest hardness.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The G ′ values at 80°C of C1, C2, and C3 were 33.31, 48.43, and 44.08 kPa, respectively. The result was agreement with the result of hardness in our previous study (Sukmanov et al, ), C2 had the highest hardness.…”
Section: Resultssupporting
confidence: 93%
“…Due to the ability of soy protein isolate to form gels with good water and oil holding capacity during heating, which improved the stability of pork meat batter and decreased the TR, WR, and FR with the increase content of soy protein isolate (Nishinari, Fang, Guo, & Phillips, ). Our previous studies also found that the water holding capacity was significantly increased with soy protein isolate increased, and the result of low field NMR exhibited that the pork batters with soy protein isolate had less water out the cooked pork batter and free water (Sukmanov et al, ), these were agreement with the emulsified stability of pork batters.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation